The Importance of Social Justice Courses in Teacher Preparation Programs - Meredith Critchfield (Journal of Scholarly Engagement)
The social justice perspective is become more popular in teacher preparation programs as a response to growing diversity in schools and to the perceived inadequacies of multicultural education. This alternative to multicultural education argues that teachers should be advocates for students and their communities, helping to address inequities in schools. This project sought to explore social justice education in more depth by examining two classes of pre-service teachers at a private Christian university in the Southwest United States. Students were asked to describe their expectations and experiences with social justice curriculum in a required social justice teacher education course. The analysis of the project’s results indicates that pre-service teachers at faith institutions must be given hands-on, practical opportunities to grapple with social justice and their faith in order to begin to understand how social justice might inform their future work as teachers.